Emotional Abuse: How the Concept Sheds Light on the Understanding of Psychological Harassment (in Quebec) - Steve Harvey; Loraleigh Keashly (Perspectives Interdisciplinaires sur le Travail et la Santé)
This paper reviews the concept of emotional abuse in the workplace and applies relevant findings and concepts to psychological harassment as defined in the legislation enacted in Quebec beginning June 1, 2004. It is noted that the terms are highly related by definition and that a clear similarity exists. Accordingly, a prospective look is taken at the challenges involved in the understanding and application of psychological harassment based on seven dimensions commonly studied and referred to in the academic literature on emotional abuse. The conclusion is that the determination of psychological harassment involves a multidimensional consideration of factors and that this gives rise to several challenges in applying the new legislation.